(untitled) (World Bulletin of Public Health, 2025)
Despite the fact that there is currently a large number of observations, the frequency of adenomyosis is increasing from year to year, while the disease is diagnosed mainly in late stages. This study will help to predict adenomyosis in the early stages and prevent severe disease. At the same time, female reproductive function is preserved